EFEKTIVITAS PENGGUNAAN MEDIA PERMAINAN ULAR TANGGA TERHADAP KEMAMPUAN ANAK DALAM MENGENAL ANGKA DI RA AL-IHYA - Lukman Hamid; Tetin Nurfitri; Lalah Nurjamilah (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2021)
Every school is always competing in making learning innovations. So that students do not get bored quikly in the learning process. A bored learning process can be one of the obstacles in the learning process. For this reason, the presentation of the game of snakes and ladders in training children’s abilities to recognize numbers can overcome children’s boredom. This study was to determine how the effectivenesss the game of snakes and ladders in training children’s ability to recognize numbers in group A RA Al-Ihya Kawalu Tasikmalaya. This study uses research and development research. Data collection techniques by interview and observation. The results showed that snakes and ladders proved effective in training children’s ability to recognize numbers.